Assessing Somatosensory Utilization during Unipedal Postural Control - Goel, Rahul; De Dios, Yiri E.; Gadd, Nichole E.; Caldwell, Erin E.; Peters, Brian T.; Reschke, Millard F.; Bloomberg, Jacob J.; Oddsson, Lars I. E.; Mulavara, Ajitkumar P. (Frontiers in Systems Neuroscience, 2017)
Multisensory - visual, vestibular, and somatosensory information is integrated for appropriate postural control. The primary goal of this study was to assess somatosensory utilization during a functional motor task of unipedal postural control, in normal healthy adults. Assessing individual bias in the utilization of individual sensory contributions during postural control may help customization of rehabilitation protocols. In this study, a test paradigm of unipedal stance control in supine orientation with and without vision was assessed. Postural control in this test paradigm was hypothesized to utilize predominantly contributions of somatosensory information from the feet and ankle joint, with minimal vestibular input. Fourteen healthy subjects “stood” supine on their dominant leg while strapped to a backpack frame that was freely moving on air-bearings, to remove available otolith tilt cues with respect to gravity that influences postural control when standing upright. The backpack was attached through a cable to a pneumatic cylinder that provided a gravity-like load. Subjects performed three trials each with eyes open (EO) or eyes closed (EC) while loaded with 60% body weight. There was no difference in unipedal stance time across the two conditions with EC condition challenging the postural control system greater than the EO condition. Stabilogram-diffusion analysis indicated that the critical mean square displacement was significantly different between the two conditions. Vestibular cues, both in terms of magnitude and the duration for which relevant information was available for postural control in this test paradigm, were minimized. These results support our hypothesis that maintaining unipedal stance in supine orientation without vision, minimizes vestibular contribution and thus predominantly utilizes somatosensory information for postural control.